Vitamin K supplementation and vascular calcification: a systematic review and meta-analysis of randomized controlled trials - Li, Te; Wang, Yun; Tu, Wei-ping (Frontiers in Nutrition, 2023)
Background: Vascular calcification is a complex process that has been linked to conditions including cardiovascular diseases and chronic kidney disease. There is ongoing debate about whether vitamin K (VK) can effectively prevent vascular calcification. To assess the efficiency and safety of VK supplementation in the therapies of vascular calcification, we performed a systematic review and meta-analysis of recent studies. Methods: We searched major databases, including PubMed, the Cochrane Library, Embase databases, and Web of Science up until August 2022. 14 randomized controlled trials (RCTs) describing the outcomes of treatment for VK supplementation with vascular calcification have been included out of 332 studies. Results were reported in the change of coronary artery calcification (CAC) scores, other artery and valve calcification, vascular stiffness, desphospho-uncarboxylated matrix Gla protein (dp-ucMGP). Reports of severe adverse events were recorded and analyzed. Results: We reviewed 14 RCTs, comprising a total of 1533 patients. Our analysis revealed that VK supplementation has a significant effect on CAC scores, slowing down the progression of CAC (I2=34%, 95% CI –17.37[–34.18, –0.56], p=0.04). The study found that VK supplementation had a significant impact on dp-ucMGP levels, as compared to the control group, where those receiving VK supplementation had lower values (I2=71%, 95% CI ¬¬¬–243.31[–366.08, –120.53], p=0.0001). Additionally, there was no significant difference in the adverse events between the groups (I2=31%, 95% CI 0.92[–0.79,1.07], p=0.29). Conclusions: VK may have therapeutic potential for alleviating vascular calcification, especially CAC. However, more rigorously designed RCTs are required to verify the benefits and efficacy of VK therapy in vascular calcification. Keywords: vitamin K, vascular calcification, coronary artery calcification, desphospho-uncarboxylated matrix Gla protein